Biofortification of Six Varieties of Lettuce (Lactuca sativa L.) With Iodine and Selenium in Combination With the Application of Salicylic Acid - Smoleń, Sylwester; Kowalska, Iwona; Kováčik, Peter; Halka, Mariya; Sady, Włodzimierz (Frontiers in Plant Science, 2019)
The agrotechnical methods of biofortification of plants, i.e., enriching them in iodine (I) and selenium (Se) could be effective methods to enrich food products in these elements. The advantage of agrotechnical methods of biofortification is the incorporation of elements in organic compounds in plants; therefore, they have better health-promoting properties than pure technical salts. Two-year studies were conducted in a greenhouse with hydroponic cultivation of three botanical varieties of lettuce in an NFT (nutrient film technique) system: two cultivars butterhead lettuces (abb. BUTL) ‘Cud Voorburgu’ and ‘Zimująca,’ two cultivars iceberg lettuces (abb. ICEL) ‘Maugli’ and ‘Królowa lata’ (all this four cultivars are classified as Lactuca sativa L. var. capitata) as well two cultivars Lactuca sativa L. var. crispa L. cultivars (abb. REDL) ‘Lollo rossa’ and ‘Redin’ having little red leaves. The study included the application of I (as KIO3), Se (as Na2SeO3), and SA into the nutrient solution. The tested treatments were as follows: (1) control, (2) I+Se, (3) I+Se+0.1 mg SA dm−3, (4) I+Se+1.0 mg SA dm−3, and (5) I+Se+10.0 mg SA dm−3. KIO3 was used at a dose of 5 mg I dm−3, while Na2SeO3 was 0.5 mg Se dm−3. Regardless of the kind of the applied compound, the highest biomass of heads was produced by the REDL ‘Redin’ variety. Furthermore, this variety, as the only one in six varieties tested, reacted with the decrease in yield to the application of I+Se and I+Se+three concentrations of SA. In the heads of all cultivars, the level of I accumulation was 10–30 times higher than of Se. The level of I accumulation formed the following order: REDL ‘Lollo rossa’ > REDL ‘Redin’ = BUTL ‘Cud Voorburgu’ > BUTL ‘Zimująca’ > ICEL ‘Maugli’ > ICEL ‘Królowa lata’. The order of Se content in leaves was as follows: REDL ‘Redin’ = BUTL ‘Cud Voorburgu’ > REDL ‘Lollo rossa’ > ICEL ‘Maugli’ > BUTL ‘Zimująca’ > ICEL ‘Królowa lata’. The obtained results indicate that the introduction of SA to the nutrient solutions in hydroponic systems may allow an improve the effectiveness of – biofortification.